THE REGIONAL GOVERNMENT POLICY OF BATAM CITY IN THE PROTECTION AND FULLFILLMENT OF THE RIGHTS OF CHILDREN AND WOMEN AGAINST DISCRIMINATORY ACTIONS - Jody Sunatoyoga; Winsherly Tan; Ampuan Situmeang (Journal of Research in Social Science and Humanities, 2025)
This research explores the policies of the Batam City Regional Government in the context of protecting and fulfilling rights of children and women against acts of discrimination. Focus on the effectiveness  policy and its implementation barriers, this study uses a qualitative approach to investigate the concrete impact  protected rights. Batam City, as an economic and industrial center, faces complex dynamics in facing the challenges of protecting the rights of children and women.  Research highlights  relevance and urgency of handling issues in regional policies.  Global and national context demonstrates the need for effective and well-implemented policies.  detailing the problem, study raises two key questions: first, this study wants to thoroughly discuss the extent of the effectiveness of policies in protecting children's and women's rights from discrimination, and second, what are the main obstacles that hinder policy implementation This type research uses empirical legal research with an approach to legislation and empirical. The findings study provide in-depth insights into implementation of the policy and impact on desired rights. This analysis highlights the complexity of social and cultural dynamics in Batam City that affect policy effectiveness. The results of this study are expected  provide  better understanding the problem of protecting the rights of children and women, provide concrete recommendations for policy improvement, and stimulate the development of further research in this field.  summarizing the findings and providing recommendations, this study has the potential to make  significant contribution to the understanding and implementation policies to protect the rights of children and women regional level.